2012
DOI: 10.1261/rna.030874.111
|View full text |Cite
|
Sign up to set email alerts
|

Structural organizations of yeast RNase P and RNase MRP holoenzymes as revealed by UV-crosslinking studies of RNA–protein interactions

Abstract: Eukaryotic ribonuclease (RNase) P and RNase MRP are closely related ribonucleoprotein complexes involved in the metabolism of various RNA molecules including tRNA, rRNA, and some mRNAs. While evolutionarily related to bacterial RNase P, eukaryotic enzymes of the RNase P/MRP family are much more complex. Saccharomyces cerevisiae RNase P consists of a catalytic RNA component and nine essential proteins; yeast RNase MRP has an RNA component resembling that in RNase P and 10 essential proteins, most of which are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
34
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 72 publications
(126 reference statements)
6
34
0
Order By: Relevance
“…However, we previously showed that coexpression of several insoluble RNase P/MRP proteins resulted in the formation of soluble and structurally homogeneous complexes (Perederina et al 2007(Perederina et al , 2010b. Yeast two-hybrid studies (Houser-Scott et al 2002), pull-down experiments (Welting et al 2004;Aspinall et al 2007), as well as our data (Khanova et al 2012; E Khanova, AS Krasilnikov, unpubl. ) indicated interactions between Pop1 and another RNase P/MRP protein component, Pop4, prompting us to consider coexpression of Pop1 and Pop4 as a possible solution to the insolubility of Pop1.…”
Section: Coexpression Of Pop1 With Pop4 Results In Soluble Pop1supporting
confidence: 65%
See 4 more Smart Citations
“…However, we previously showed that coexpression of several insoluble RNase P/MRP proteins resulted in the formation of soluble and structurally homogeneous complexes (Perederina et al 2007(Perederina et al , 2010b. Yeast two-hybrid studies (Houser-Scott et al 2002), pull-down experiments (Welting et al 2004;Aspinall et al 2007), as well as our data (Khanova et al 2012; E Khanova, AS Krasilnikov, unpubl. ) indicated interactions between Pop1 and another RNase P/MRP protein component, Pop4, prompting us to consider coexpression of Pop1 and Pop4 as a possible solution to the insolubility of Pop1.…”
Section: Coexpression Of Pop1 With Pop4 Results In Soluble Pop1supporting
confidence: 65%
“…The size of Pop1, its presence exclusively in the eukaryotic RNases P/MRP Marvin and Esakova and Krasilnikov 2010;Jarrous and Gopalan 2010), the effects of Pop1 mutations on the holoenzymes' assembly (Lygerou et al 1994;Chamberlain et al 1998;Xiao et al 2006), and the apparent spread of the RNase P/MRP RNA regions involved (directly or not) in interactions with Pop1 (Ziehler et al 2001;Houser-Scott et al 2002;Hipp et al 2012;Khanova et al 2012), are all consistent with a potential central role played by Pop1 in the stabilization of the global structure of the RNA components of eukaryotic RNases P/MRP. However, insolubility of individually expressed Pop1 (Ziehler et al 2001;Xiao et al 2006) has previously hindered direct studies of this protein and its interactions with other RNase P/MRP components.…”
Section: Introductionmentioning
confidence: 62%
See 3 more Smart Citations